Visualizing Qualitative Data in Evaluation Research. Issue 139 (18th September 2013) - Henderson, Stuart; Segal, Eden H.
Abstract: This chapter introduces data visualization techniques for qualitative data. These techniques can be used in most stages of evaluations, including early planning and design, data analysis, and reporting. Qualitative data visualization can also be used in different approaches to evaluation, for instance, traditional process and summative, developmental, utilization, participatory, and mixed‐methods evaluations. The authors first describe a conceptual framework for understanding the different types of qualitative data visualizations before providing examples of visualizations in various evaluation contexts. The chapter concludes with a discussion of challenges or issues evaluators should consider when visualizing qualitative data. © Wiley Periodicals, Inc., and the American Evaluation Association.